Performance of strawberry cultivars subjected to different types of pollination in a greenhouse - Witter, Sidia; Radin, Bernadete; Lisboa, Bruno Brito; Teixeira, Juliana Galaschi; Blochtein, Betina; Imperatriz-Fonseca, Vera Lucia (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the effects of different types of pollination on the fruit quality of strawberry cultivars, and their isolated contribution to fruit mass, as well as to determine the potential of Plebeia nigriceps (Hymenoptera: Apidae, Meliponini) as a pollination agente in protected environment. The cultivars Aromas, Diamante, and Cegnidarem were subjected to self‑pollination, pollination by P. nigriceps, and free pollination treatments. The experiments were carried out in a “pampeana” greenhouse, covered with transparent polyethylene and without anti‑insect screens on the sides, with 1,344 plants. For the evaluations, 56 primary flowers of each cultivar, still in bud, were marked, and each of these plants was considered a replicate. Fresh matter mass, weight, diameter, and misshape incidence in fruit were evaluated. The contribution of Entomophilous pollination on fruit weight varies according to the cultivar. Cultivars have different sensibility to self‑pollination, regarding misshape incidence on fruit. Entomophilous interference on strawberry yield is more related to reduction of misshape incidence than to increases in fruit mass itself. P. nigriceps behavior indicates that this species has good potential for pollinating strawberry crop in protected environment.